Asia's Stock Markets : Are There Crouching Tigers and Hidden Dragons? - Lipinsky, Fabian (IMF Working Papers; Working Paper, 2014)
Stock markets play a key role in corporate financing in Asia. However, despite their increasing importance in terms of size and cross-border investment activity, the region's markets are reputed to be more 'idiosyncratic' and less reliant on economic and corporate fundamentals in their pricing. Using a model that draws on international asset pricing and economic theory, as well as accounting literature, we find evidence of greater idiosyncratic influences in the pricing of Asia's stock markets, compared to their G-7 counterparts, beyond the identified systematic factors and local fundamentals. We also show proof of a significant relationship between the strength of implementation of securities regulations and the 'noise' in stock pricing, which suggests that improvements in the regulation of securities markets in Asia could enhance the role of stock markets as stable and reliable sources of financing into the future.